The intensively enhanced conductivity of polyelectrolytes by amphiphilic compound doping1. Issue 14 (14th April 2015) - Hsu, Huang-Ming; Hsu, Chun-Han; Kuo, Ping-Lin
<x xml:space="preserve">Abstract</x> A simple amphiphilic compound, pyrenesulfonic acid (PSA), interacts with the hydrophobic moiety of a copolymer (sulfonated poly(styrene-b-isoprene-b-styrene), s-SISH) and simultaneously provides hydrophiles of –SO3H. Doping 2% PSA to the membranes of s-SISH enhances its very low conductivity by 26 times from 2.0 × 10−3 S cm−1 to 5.3 × 10−2 S cm−1.